Significance of transvaginal Doppler ultrasonography for detection of malignant gestational trophoblastic disease - Nikolić Branka; Rakić Snežana; Pavlović Dejan; Popovac Svetlana; Lukić Relja (Vojnosanitetski Pregled)
Transvaginal Doppler ultrasonography has an important role in detecting and confirming the gestational trophoblastic disease (GTD). It can also be helpful in early detection of the malignant cases of GTD such as the invasion and protrusion of trophoblastic tissue into the uterine wall. Ultrasonographic picture of the malignant GTD is also specific for the presence of prominent zones of vasculavization in the peritrophoblastic tissue, as well as in the uterine tissue in which malignant GTD is developed. Resistance Index (RI) values were measured at the level of blood vessels of peritrophoblastic tissue and of suspected zones in the uterine tissue to detect neovascularization, which followed the malignant process. Theca luteal cysts were often detected by Transvaginal Doppler ultrasonography.